Not for profit sponsorship - Minton, Graham (Henry Stewart Talks, 2009)
Defining not for profit organizations and corporate social responsibility (CSR), Why are businesses interested in not for profit organizations and CSR?, What are the trends in not for profit sponsorship, How do they differ from traditional sponsorships?, Successful case studies